2013
DOI: 10.15376/biores.9.1.105-119
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Norway Spruce: Intra-Ring Variation and Generic Behavior of Earlywood and Latewood until Failure

Abstract: The alternating earlywood and latewood growth ring structure has a strong influence on the mechanical performance of Norway spruce. In the current study, tensile tests in the longitudinal and tangential directions were performed on a series of specimens representing one growth ring at varying relative humidities. All tested mechanical parameters, namely modulus of elasticity and ultimate tensile stress, followed the density distribution in the growth ring, with the minimum values in earlywood and the maximum v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 33 publications
1
13
0
1
Order By: Relevance
“…Both Dinwoodie (2000) and Sugiyama (1967), using higher loading rates (2 days-2 years), determined that, as a result of creep, the mechanical properties of wood were influenced by the loading rate. Lanvermann et al (2014), however, reported that, because of the high local variability of the values, the mechanical properties were not significantly decreased. Moreover, Dinwoodie (2000) concluded that the effect of the loading rate depended on the size of the sample and that the rate was higher in structural timber than in small, clear specimens.…”
Section: Resultsmentioning
confidence: 95%
“…Both Dinwoodie (2000) and Sugiyama (1967), using higher loading rates (2 days-2 years), determined that, as a result of creep, the mechanical properties of wood were influenced by the loading rate. Lanvermann et al (2014), however, reported that, because of the high local variability of the values, the mechanical properties were not significantly decreased. Moreover, Dinwoodie (2000) concluded that the effect of the loading rate depended on the size of the sample and that the rate was higher in structural timber than in small, clear specimens.…”
Section: Resultsmentioning
confidence: 95%
“…Micro-scale sized samples have been used to determine the mechanical properties of earlywood and latewood sections, wood strands, and fibers Cramer et al 2005;Kretschmann et al 2006;Hindman and Lee 2007;Jeong 2008;Jeong et al 2009;Lanvermann et al 2014;Roszyk et al 2016). Cramer et al (2005) determined the elastic properties of EW and LW (longitudinal modulus of elasticity, shear modulus) in loblolly pine wood.…”
Section: Introductionmentioning
confidence: 99%
“…Both Dinwoodie (2000) and Sugiyama (1967), using lower loading rates (2 days-2 years), determined that, as a result of creep, the mechanical properties of wood were influenced by the loading rate. Lanvermann et al (2014), however, reported that, because of the high local variability of the values, the mechanical properties were not significantly decreased. Moreover, Dinwoodie (2000) concluded that the effect of the loading rate depended on the size of the sample and that the rate was higher in structural timber than in small, clear specimens.…”
Section: Resultsmentioning
confidence: 95%